King's Birthday Generates Funds for Charity - Golf, Malaysia (Golf Malaysia, 2013)
A Charity Golf Tournament was held in commemoration of His Majesty the Seri Paduka Baginda Yang Dipertuan Agong's 84th birthday on 19th of December 2012.